The clusters growth and evaporation rate constante calculation by using of molecular dynamics method for condensation behind the shock front - Insepov, Z.; Karatajev, E. M. (Matem. Mod., 1993)
Molecular dynamics model of calculation of the growth and evaporation rate constants of dusters is proposed. Calculations for small clusters are carried out. On the basis of the chemical mechanism the characteristic time of condensation is achieved, which is in available agreement with experiment on condensation of iron vapors behind the shock front.
Keywords: clusters growth; evaporation rate; molecular dynamics; condensation